2009
DOI: 10.1161/atvbaha.108.183251
|View full text |Cite
|
Sign up to set email alerts
|

CD146 and its Soluble Form Regulate Monocyte Transendothelial Migration

Abstract: Objectives-During inflammation, cell adhesion molecules are modulated or redistributed for leukocyte transmigration.Among molecules at the interendothelial junction, CD146 is involved in cell-cell cohesion and permeability, but its role in monocyte transmigration is unknown. Methods and Results-TNF enhanced CD146 expression at the junction and apical membrane of human umbilical veins endothelial cells (HUVECs) through CD146 synthesis and intracellular store redistribution. In addition, TNF increased the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
123
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 114 publications
(136 citation statements)
references
References 34 publications
9
123
0
4
Order By: Relevance
“…Altogether, these results suggest that both soluble and membrane CD146 are able to bind different proteins as a function of the cellular and physiopathological context but that heterophilic interactions are favored. Of interest, we found angiomotin mRNA expression (data not shown) not only in endothelial cells as HUVEC and EPC but also in the trophoblastic cell line HTR-8/SVneo, in L929 fibroblastic cells and in the monocytic cell line THP1, which does not express membrane CD146 but was activated by sCD146 during transmigration (4). Identifying angiomotin expressing cells will presumably provide new target cells for sCD146.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Altogether, these results suggest that both soluble and membrane CD146 are able to bind different proteins as a function of the cellular and physiopathological context but that heterophilic interactions are favored. Of interest, we found angiomotin mRNA expression (data not shown) not only in endothelial cells as HUVEC and EPC but also in the trophoblastic cell line HTR-8/SVneo, in L929 fibroblastic cells and in the monocytic cell line THP1, which does not express membrane CD146 but was activated by sCD146 during transmigration (4). Identifying angiomotin expressing cells will presumably provide new target cells for sCD146.…”
Section: Discussionmentioning
confidence: 88%
“…However, until recently, its physiological role was unknown. In a previous report, we have shown that sCD146 is involved in inflammation by specifically binding to monocytes and thereby stimulating transendothelial migration (4). We have further shown that sCD146 is also involved in angiogenesis (5).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Indeed, we showed that sCD146 significantly increases the transmigration of monocytes across the monolayer of endothelial cells. 2 We also demonstrated the angiogenic properties of the molecule. Soluble CD146 increased endothelial proliferation, migration and vascular tube formation.…”
mentioning
confidence: 69%